Unlocking public sector excellence: The synergy of intellectual capital and digital leadership in tax administration - Amrie Firmansyah; Ferry Irawan; Suparna Wijaya (Intangible Capital)
Purpose: This study investigates the impact of intellectual capital, specifically public human capital, public relational capital, and public structural capital, on the Directorate General of Taxes (DGT) organizational performance in Indonesia. It also examines the moderating role of digital leadership in enhancing these relationships.